2018
DOI: 10.1016/j.smim.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular complement activation—An alarm raising mechanism?

Abstract: It has become increasingly apparent that the complement system, being an ancient defense mechanism, is not operative only in the extracellular milieu but also intracellularly. In addition to the known synthetic machinery in the liver and by macrophages, many other cell types, including lymphocytes, adipocytes and epithelial cells produce selected complement components. Activation of e.g. C3 and C5 inside cells may have multiple effects ranging from direct antimicrobial defense to cell differentiation and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 161 publications
(132 reference statements)
3
53
0
1
Order By: Relevance
“…However, the immune cell infiltration did not differ from samples obtained from non-aneurysmatic atherosclerotic thoracic aortas, underscoring the need for appropriate controls when studying non-syndromic TAA. Interestingly, however, C5aR2 in media of TAA patients were colocalised with T cells and macrophages showing intracellular localisation in both cell types, as also have been reported by others in others in various tissues 35. Verghese et al have recently reported that C5aR2 augment the activation of regulatory T cells promoting cardiac allograft survival in an experimental mouse model, supporting an anti-inflammatory role of C5aR2 also within the T cell population 36.…”
Section: Discussionsupporting
confidence: 70%
“…However, the immune cell infiltration did not differ from samples obtained from non-aneurysmatic atherosclerotic thoracic aortas, underscoring the need for appropriate controls when studying non-syndromic TAA. Interestingly, however, C5aR2 in media of TAA patients were colocalised with T cells and macrophages showing intracellular localisation in both cell types, as also have been reported by others in others in various tissues 35. Verghese et al have recently reported that C5aR2 augment the activation of regulatory T cells promoting cardiac allograft survival in an experimental mouse model, supporting an anti-inflammatory role of C5aR2 also within the T cell population 36.…”
Section: Discussionsupporting
confidence: 70%
“…The complement system was originally revealed as a heatsensitive element in fresh serum that "complemented" the effects of particular antibody during the lysis of red blood cells and bacteria (West et al, 2018). It is an important effector of the humoral immunity (Noris and Remuzzi, 2013) and represents a highly integrative system with a number of functions, including removal of injured cells and debris, host defense, regenerative processes, modulation of metabolism, and regulation of adaptive immunity (Reichhardt and Meri, 2018). Ginsenan, acidic polysaccharides To deplete NK cells in vivo, rabbit anti-asialo GM1 serum was injected into mice 1 and 3 days before inoculation of B16BL6 melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, C3aR signaling was found to be involved in the induction of in ammatory cytokines [25], proliferation of mesangial [11] and carcinoma cells [12] and EMT of tubular epithelial cells [10]. Recently, C3aR signaling was believed to be an important factor in maintaining cellular homeostasis [26][27].…”
Section: Discussionmentioning
confidence: 99%